Co-infection of Mycoplasma genitalium and Chlamydia trachomatis in an infertile female patient with genital tuberculosis - Prathyusha Kokkayil; Jyoti Rawre; Neena Malhotra; Benu Dhawan (Wolters Kluwer Medknow Publications, 2013)
Genital tuberculosis is a common cause of female infertility in India. But, it is important to screen for other agents like Chlamydia trachomatis and genital Mycoplasmas as well to avoid persistence of infection and its long-term sequelae. Timely diagnosis of these infections using nucleic acid amplification tests and institution of appropriate therapy will improve the conception rates in infertile women. We report a case of co-infection of Mycoplasma genitalium and Chlamydia trachomatis in an infertile female patient with genital tuberculosis. The infections were diagnosed using polymerase chain reaction, and the patient responded to a combination of antituberculosis therapy and 1 g single-dose Azithromycin.